Character Cards: A gender-responsive, people-centered training tool - Kadry, Salma; Campbell, Raramai (CGIAR, 2025)
Character Cards merge art, storytelling, and research to build awareness and understanding on how climate risks, vulnerabilities, and resilience intersect and differ across gender, identity, and geography. The game features 12 characters—each portraying a unique lived experience shaped by climate, peace, security, and displacement contexts